Management of Digital Services During Covid-19 in the Library of Medical University of Pleven - Georgiev, Gabriel (Bobcatsss, 2023)
During Covid-19, libraries face enormous challenges and requirements. Some of them have started offering new and stable online opportunities for their users. As part of the international library space, the Library of Medical University of Pleven (L at MU-Pleven) created new online services and consolidated proven ones. They emerged as a kind of a meaningful and purposeful project for managing digital resources during an epidemiological situation, and the need for their management is palpable. The subject of the present study is the digital services, provided by the Library of MU – Pleven, such as: remote extension of the term for rewriting; constant communication with a librarian through the social network Facebook and e-mail; increasing the Digital Collections at the request of student teachers; online-re-registration in order to provide access to digital content; information mediation - providing addresses of free databases. Particular attention is paid to the cooperation with the research department. We assist in obtaining remote access to the Scopus database and the Web of Science of doctoral students, postgraduates and lecturers, in order to continue the scientific activity. The methodology of conducting the research is based on taking an online interview. Each of the librarians is tasked to do a specific task - to manage a particular digital service. A linear management structure has been created. Each of the subordinates receives orders from only one head - director of the library - above him and reports only to him. Formal connections are made through direct contacts. This ensures the stability of the relationship between co- workers and the responsibility is individual. The conclusion from the research is that, unfortunately, there are no trained staff to react in atypical situations such as period of social isolation due to the COVID-19 pandemic, but it is necessary to transform positions into "moves". That is why we have chosen a simplified management model that can be changed in the future. Although slightly "primitive", we think that simple things are more digestible and easy to implement. Thus, an unprepared user or staff member will be able to adapt fast. We hope that this will be in favour of some libraries that decide to follow our example.